Coaching excellence - Pyke, FraNK (Human Kinetics, 2013)
No single resource can convey everything that a coach should know and do. So Coaching Excellence does the next best thing: it builds on the basics to provide you with a wealth of information so you can become more adept in your role as an excellent coach. Eighteen experts offer the best knowledge, research and insights that you can apply in working with your athletes, players and teams. Throughout the text, you will find proven strategies, advice and insights. From evaluating and teaching skills to motivation, nutrition and safety, Coaching Excellence is the complete guide to becoming a complete coach.